ILUSTRASI DIGITAL UNTUK SEMUA: PEMBERDAYAAN KREATIVITAS DAN KEADILAN GENDER DI SEKOLAH DASAR DALAM SEMANGAT SDG - Chandra, Edy; Nero Devanca Chandra; Luvena Valencia Ciputra; Naomi Gracia Wijaya; Daisy Alicia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
This community service program was implemented at SD Sinar Dharma, Jakarta, to address the digital visual literacy gap that has become increasingly urgent in primary education. Conducted from January to April 2025, the program comprised ten training sessions in digital illustration, each lasting ninety minutes, and employed a practice-based participatory learning approach designed to foster active student engagement in the creative process. The thematic curriculum integrated technical competencies—such as the application of layers, digital brushes, coloring, lighting, and composition—with conceptual dimensions of character development, local cultural representation, and narrative construction. Evaluation relied on a rubric encompassing five criteria: originality of ideas, technical accuracy, expressive quality, thematic relevance, and active participation. Data were collected through direct classroom observation, brief interviews, and analysis of student-produced digital works. Results demonstrated significant learning progress: by the fifth session, more than 70 percent of students successfully applied layered coloring techniques and basic lighting effects. Female students constituted 72 percent of participants and, on average, outperformed male students by 12.5 points in originality and technical completion, suggesting that the program fostered a safe and gender-inclusive learning environment. The initiative contributes directly to Sustainable Development Goals 4 (quality and inclusive education) and 5 (gender equality), while offering practical implications for replication across schools, teacher capacity building, thematic curriculum integration, and the establishment of digital galleries to enhance recognition and appreciation of student achievements. ABSTRAK Program Pengabdian kepada Masyarakat ini diselenggarakan di SD Sinar Dharma, Jakarta, dengan tujuan menjembatani kesenjangan literasi visual digital yang semakin relevan dalam ekosistem pendidikan dasar. Kegiatan dilaksanakan pada periode Januari–April 2025 melalui sepuluh sesi pelatihan ilustrasi digital, masing-masing berdurasi 90 menit, menggunakan pendekatan practice-based participatory learning yang menekankan keterlibatan aktif peserta dalam proses kreatif. Kurikulum tematik dirancang secara berlapis, menggabungkan keterampilan teknis—seperti penggunaan layer, kuas digital, pewarnaan, pencahayaan, dan komposisi—dengan keterampilan konseptual berupa pengembangan karakter, pengenalan budaya lokal, serta konstruksi narasi visual. Instrumen evaluasi menggunakan rubrik dengan lima indikator utama: orisinalitas ide, ketepatan teknik, ekspresi visual, relevansi tema, dan tingkat partisipasi. Data diperoleh melalui observasi kelas, wawancara singkat, serta analisis karya digital yang dihasilkan siswa. Hasil menunjukkan peningkatan signifikan: sejak sesi kelima, lebih dari 70% siswa mampu mengaplikasikan teknik pewarnaan berlapis dan pencahayaan sederhana. Tingkat partisipasi perempuan mencapai 72% dengan rerata skor 12,5 poin lebih tinggi pada aspek orisinalitas dibandingkan siswa laki- laki, menunjukkan terciptanya ruang belajar yang aman, setara, dan inklusif. Program ini berkontribusi langsung pada pencapaian SDG 4 (pendidikan berkualitas inklusif) dan SDG 5 (kesetaraan gender), serta membuka peluang replikasi pada sekolah lain melalui penguatan kapasitas guru, integrasi kurikulum tematik, dan pemanfaatan galeri digital sebagai medium apresiasi karya..